Evaluation of scar penetrating neovascularisation in a rat epigastric flap model - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2015)
Aim: The aim of this study is to investigate neovascularisation patterns in the presence of scar tissue and to compare the venous vs arterial components of the scar penetrating neovascularisation. Methods: Forty male Spraque-Dawley Rats, which were divided into four groups, were used for this study. At the beginning of the study a vertical midline abdominal incision was made to all animals. Six weeks after the incisions were made, epigastric flaps based on inferior epigastric vessels were raised. In the first group both left and right epigastric artery and veins were protected. In the second group only the right epigastric artery and vein was protected. In the third group, besides the right epigastric artery and vein, only the left epigastric artery was kept intact. In the fourth group, besides the right epigastric artery and vein, only the left epigastric vein was kept intact. Results: The percentages of necrotic areas on the flaps were statistically evaluated. The percentages of the necrotic areas on the left side of the flaps were significantly higher in the second group (p = 0.0305). Total flap area necrosis was also significantly higher in the second group (p = 0.026). In each group, vessel formations were identified which were extending through the midline scar tissue in the angiographic evaluations. Conclusions: These results suggest that scar penetrating neovascularisation on an epigastric flap with one sided pedicle, which is supported by a vein or an artery on the contralateral side, can be enough to facilitate the flap circulation.
Keywords: Microvascular; flaps; angiogenesis; neovascularisation; scar; epigastric flap; OZONE THERAPY; IMPROVES SURVIVAL; PROTECTION